Triterpenoids. Issue 2 (24th October 2014) - Hill, Robert A.; Connolly, Joseph D.
Abstract : This review covers the isolation and structure determination of triterpenoids reported during 2012 including squalene derivatives, lanostanes, holostanes, cycloartanes, cucurbitanes, dammaranes, euphanes, tirucallanes, tetranortriterpenoids, quassinoids, lupanes, oleananes, friedelanes, ursanes, hopanes, serratanes, isomalabaricanes and saponins; 348 references are cited. Abstract : Covering: 2012. Previous review: Nat. Prod. Rep ., 2013, 29, 1028–1065 This review covers the isolation and structure determination of triterpenoids reported during 2012 including squalene derivatives, lanostanes, holostanes, cycloartanes, cucurbitanes, dammaranes, euphanes, tirucallanes, tetranortriterpenoids, quassinoids, lupanes, oleananes, friedelanes, ursanes, hopanes, serratanes, isomalabaricanes and saponins; 348 references are cited.